Peningkatan Kualitas Pembelajaran di Madrasah - Wardatul Janah; Leppe Firmansyah; Dessy Eka Citra Dewi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Improving the quality of learning in madrasas is a strategic and sustainable effort that includes various aspects, starting from developing a contextual and integrative curriculum, improving the competence of teaching staff, to optimal utilization of educational technology. In the context of globalization and rapid development of science, madrasas are required not only to maintain their Islamic identity, but also to be able to produce graduates who are competent, have character, and are adaptive to the challenges of the times. Therefore, learning in madrasas needs to be designed holistically, integrating spiritual, moral, and intellectual values ​​with an innovative and participatory pedagogical approach. In addition, support from various parties such as the government, society, and religious institutions is an important factor in creating a superior and competitive madrasa education ecosystem. With these steps, it is hoped that madrasas can become educational institutions that are not only relevant to the needs of the times, but also make a significant contribution to producing a generation that is knowledgeable, moral, and highly competitive.